Percutaneous Antegrade Transvenous Variceal Obliteration for Portal Vesiculopathy-Related Gross Hematuria - N., Salal; Shaw, Amar Narayan; Chatterjee, Pritam; Ravikumar, Radhakrishnan (Journal of Clinical Interventional Radiology ISVIR, 2023)
Vesical varices secondary to portal hypertension are extremely rare cause of hematuria with only a few cases reported to date. We report a case of portal vesiculopathy in a patient of hepatitis B virus-related chronic liver disease presenting with gross hematuria, successfully treated with percutaneous antegrade transvenous obliteration using n-butyl cyanoacrylate glue and Amplatzer vascular plug.
Keywords: vesical varices; portal hypertension; hematuria